Islamic Expressions On The Culprits Of Islamic Centers In East Kalimantan - Diajeng Laily Hidayati; Ida Suryani Wijaya (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
The aim of this paper is to (1) explore the dynamics within the implementation of religious sermon in the culprit of Islamic Centers and Mosques in East Kalimantan, and (2) to assess how Da’is and board of Islamic Centers and Mosques contruct the concept of Ideal Da’wa thus what topics should be promoted and what topics should be avoided. Findings of this paper reveal that the implementation of religious sermons in Islamic Centers in East Kalimantan aims at representing the many mosques within the region where the Islamic Center stands. Islamic Center is suppose to play the role model of ideal mosque and every mosque in the region must revitalize its role and functions to become those of the Islamic Centers. However, Islamic Centers in East Kalimantan are not successful enough in representing the many mosques it claims to represent due to explicit rules on who can and cannot gives sermon in the culprit of those Islamic Centers.